Photochemie [Bookplate featuring Matthew Carey Lea] - Plotnikov, I. S. (Ivan Stepanovich). (W. Knapp, 1910)
Franklin Institute Library bookplate featuring a small inset portrait of Matthew Carey Lea (1823-1897). Lea, a Philadelphian lawyer and scientist, was devoted to the chemistry of photography. He is known as the father of mechanochemistry due to his observations of silver halide decomposition by trituration. After his death, Lea's notebooks were destroyed as per his request, and his books and apparatus were bequeathed to the Franklin Institute.
Keywords: Bookplates; Lea, M. Carey (Mathew Carey), 1823-1897; Photochemistry; Mechanical chemistry; Franklin Institute (Philadelphia, Pa.); Photographic chemistry; Photography--Printing processes--Silver; Metal clusters